2014
DOI: 10.1002/14651858.cd003039.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Colony-stimulating factors for chemotherapy-induced febrile neutropenia

Abstract: Trusted evidence. Informed decisions. Better health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
77
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(86 citation statements)
references
References 60 publications
1
77
0
3
Order By: Relevance
“…Granulocyte colony‐stimulating factor (G‐CSF) was not used systematically in our cohort. Although a meta‐analysis showed that its use in patients with chemotherapy‐induced neutropenia had no effect on overall mortality, these data were mostly obtained from patient series in developed countries, where the toxic mortality rates are already low, and a different impact might be seen in settings like ours, with higher mortality rates during neutropenia. Administering G‐CSF might also reduce the interval between cycles, thereby allowing higher‐intensity early doses, and its use is under consideration by our group.…”
Section: Discussionmentioning
confidence: 99%
“…Granulocyte colony‐stimulating factor (G‐CSF) was not used systematically in our cohort. Although a meta‐analysis showed that its use in patients with chemotherapy‐induced neutropenia had no effect on overall mortality, these data were mostly obtained from patient series in developed countries, where the toxic mortality rates are already low, and a different impact might be seen in settings like ours, with higher mortality rates during neutropenia. Administering G‐CSF might also reduce the interval between cycles, thereby allowing higher‐intensity early doses, and its use is under consideration by our group.…”
Section: Discussionmentioning
confidence: 99%
“…The main method of prophylaxis for febrile neutropenia or reduction of neutropenia duration after cytostatic therapy is prophylactic administration of granulocyte colony-stimulating factors (G-CSFs) -proteins that specifically stimulate hematopoietic progenitor cells of myeloid focus and accelerate production of normal neutrophils [1,2,7,16,17,18,21].…”
Section: Introductionmentioning
confidence: 99%
“…The decreasing mortality rates in the recent years could be attributed to the development of effective treatment modalities of febrile neutropenia and improvement in systems aimed at the early detection of sepsis patients [6]. The use of newer less toxic chemotherapy regimens along with prophylactic/therapeutic colony-stimulating factors may also play a role, although the benefit of therapeutic colony-stimulating factors for reducing mortality among patients with febrile neutropenia remains unclear [14,15]. Also, the differences in patient characteristics, comorbidities, and types of infection may also have accounted for some of the differences, which could not be separately analyzed in the present study.…”
mentioning
confidence: 99%